Development of motion graphic animation videos on the material for compiling cladograms for class X - Ariska Eka Saputri; Much. Fuad Saifuddin (Master Program of Biology Education, Universitas Lambung Mangkurat, 2022)
A cladogram is a matter of the presence or absence of kinship living things in a group. Cladograms are often found in everyday life, but the teacher cannot provide maximum examples to students due to limited time and teaching materials in classroom learning. This study aimed to find motion graphic animation video media for the odd semester X MIPA cladogram material. This research and development research with a 4-D development model (four D) define, design, develop, and disseminate. The data collection technique used a questionnaire with a Likert scale. Validation was carried out by media experts, material experts, and small and large group assessments and trials on students. The study results said that the validation of media experts obtained a percentage of 86.67%. Material expert validation obtained a proportion of 66.67%. The teacher's assessment obtained a percentage of 95%. The response of 10 students of class X MIPA 2 in the small group trial obtained 83.19%. Meanwhile, in the large group trial with a response of 30 students of class X MIPA 1, the proportion was 84.55%. So, the motion graphic animation video of the cladogram material is declared suitable for use in learning.AbstrakKladogram merupakan materi ada atau tidaknya hubungan kekerabatan makhluk hidup di dalam suatu kelompok. Kladogram banyak dijumpai dalam kehidupan sehari-hari, namun karena adanya keterbatasan waktu dan bahan ajar dalam pembelajaran di kelas guru belum dapat memberikan contoh yang maksimal kepada siswa. Tujuan penelitian ini untuk menguji kelayakan media video animasi motion graphic materi kladogram X MIPA semester ganjil. Penelitian ini merupakan penelitian pengembangan (Research and Development) dengan model pengembangan 4-D (four D), yaitu define (pendefinisian), design (perancangan), develop (pengembangan), dan disseminate (penyebaran). Teknik pengumpulan data menggunakan angket dengan skala Likert. Validasi dilakukan oleh ahli media, ahli materi, dan penilaian pendidik serta uji coba kelompok kecil dan besar pada siswa. Hasil penilaian validasi dari ahli media 86,67%, ahli materi 66,67%, dan guru 95%. Respon dari 10 siswa kelas X MIPA 2 pada uji coba kelompok kecil memperoleh persentase 83,19%. Sedangkan, pada uji coba kelompok besar dengan respon 30 siswa kelas X MIPA 1 memperoleh persentase 84,55%. Maka, video animasi motion graphic materi kladogram dinyatakan layak digunakan untuk pembelajaran.